Identification of Meloidogyne species associated with upland ornamentals plants in Costa Rica. - Solano-González, Stefany (2015)
The objective of this study was to identify nematodes species of the genus Meloidogyne associated with upland ornamental plants. We sampled ten ornamental species in a commercial nursery in San Isidro, Heredia, Costa Rica between 2011-2012. Morphometric measurements of the stylet length, the tail length, and the hyaline region of J2s, as well as perineal patterns of egg-carrying females were used for identification, Genomic DNA was extracted from single J2s and molecular analyses were performed by amplifying the intergenic region between cytochrome oxidase subunit II of the COII and the long subunit of the ARN ribosomal genes by PCR-RFLP. Combining these methods allowed identification of five species of nematodes of the genus Meloidogyne (M. arenaria, M. hapla, M. hispanica, M. incognita and M. javanica), and new restriction enzyme patterns were reported for M. hapla and M. javanica using AluI. Additionally, a preliminary report of M. hispanica was described by sequencing the 28S and 18S regions.